Effects of two dietary protein levels on growth, body composition, intestinal microflora and expression of TOR, IGF‐I, LPL and HSP70 of juvenile silver sillago, Sillago sihama. (1st November 2021) - Liu, Hao; Dong, Xiaohui; Tan, Beiping; Du, Tao; Zhang, Shuang; Yang, Yuanzhi; Chi, Shuyan; Yang, Qihui; Liu, Hongyu
Abstract: The purpose of this study was to estimate the effects of two diets on the growth, body composition, intestinal microbiota and gene expression of juvenile silver sillago, Sillago sihama . Silver sillago was fed a diet with either protein 400 g/kg (P40 group) or protein 500 g/kg (P50 group). 180 healthy fish (average wt. 0.83 ± 0.01 g) were equally distributed in two treatments in triplicates with 30 fish per tank. Following an 8‐week feeding study, the results showed that the protein efficiency ratio (PER) was significantly higher in the P40 group than that in the P50 group ( p < .05). Among the morphological parameters, condition factor (CF) was significantly higher in the P40 group and the hepatosomatic indices (HSI) was significantly higher in the P50 group. Whole‐body moisture was significantly higher in the P40 group than that in the P50 group, while whole‐body ash was just the opposite of moisture. From histological sections of the liver, the P50 group had large lipid deposits in the liver. In the fish liver, lipoprotein (LPL) expression was significantly decreased in the P50 group, while heat shock protein 70 (HSP70) was significantly increased in the P50 group. At the phylum level, the relative abundance of Bacteroidetes and Verrucomicrobia was significantly lower in the P40 group. At the family level, the abundance of Lachnospiraceae and Halomonadaceae was lower in the P40 group. The most significantly changed pathways between the two groups were metabolism and environmental information processing. In conclusion, the P50 group was superior to the P40 group in all growth parameters and intestinal flora structure; however, the high‐protein level of the diet can lead to the deposition of excess lipids in the liver and create some metabolic stress.